Euglesa kolymensis Bespalaya, Aksenova & Bolotov 2024, sp. nov. - Bespalaya, Yulia V.; Vinarski, Maxim V.; Aksenova, Olga V.; Babushkin, Evgeniy S.; Gofarov, Mikhail Yu.; Kondakov, Alexander V.; Konopleva, Ekaterina S.; Kropotin, Alexander V.; Mabrouki, Youness; Ovchankova, Nadezda B.; Palatov, Dmitry M.; Sokolova, Svetlana E.; et al. (Zenodo, 2023)
Euglesa kolymensis Bespalaya, Aksenova & Bolotov sp. nov. (Fig. 11A) Zoobank number: urn:lsid:zoobank.org:act: BDC94015-12D0- 42CB-B21E-F7C950E94EFD. Type series: The holotype is deposited in RMBH (accession number: MSph-787). The type series includes one holotype. Type locality: Russia: Yakutia, Srednekolymsk, lake next to the oil depot, Kolyma River Basin, [67°27 ʹ 29″N 153°42 ʹ 22″E], 25. VI.2021, Sokolova & Zubrii leg. Etymology: This species is named after the Kolyma River. Description: Shell round-oval in shape, its length is 4.7 mm (Fig.11A). The beaks are rounded and slightly protruding, somewhat shifted to the posterior edge of the shell (Fig.11A). The cardinal tooth of the right valve slightly curved has a thickening at the ends, the posterior end is branched. The cardinal teeth of the left valve are straight parallel to each other (Fig. 12C). The inner cardinal tooth of the left valve is thickened. Distribution: Eastern Siberia, Kolyma River Basin. Comments: The 16S and 28S rRNA sequences of this species have no analogues in GenBank and form a clade sister to the E. globularis group (Fig. 2). Considering that E. kolymensis was found in the Kolyma River Basin, we also analysed the original descriptions, and compared our material with the type specimens of some nominal species described from the same river basin: Euglesa czerskii (Starobogatov & Streletskaja, 1967), Euglesa jacutica (Starobogatov & Streletskaja, 1967), and Euglesa rotundicostata (Starobogatov & Streletskaja, 1967) (Supporting Information, Fig. S1A, L, M). The original morphological descriptions and features of these type specimens do not correspond to those of our specimen from the Kolyma River. In addition, all the listed species were subsequently assigned to the genera Henslowiana , Cingulipisidium , and Cyclocalyx according to Korniushin (1996) that are clearly different from the E. globularis group (see Vinarski and Kantor 2016). Differential diagnosis: The new species can be distinguished from its sister species ...